2021
DOI: 10.3390/electronics10172138
|View full text |Cite
|
Sign up to set email alerts
|

Realization of Low-Voltage and High-Current Rectifier Module Control System Based on Nonlinear Feed-Forward PID Control

Abstract: The low-voltage and high-current permanent magnet synchronous generator (PMSG), which has characteristics of high power density, small size, and excellent energy saving, is representative of the generators. As a key module of the integrated DC output system of PMSG, the low-voltage and high-current rectifier module is also a nonlinear time-varying system that is readily influenced by parametric changes and external disturbances. Aiming at the shortcomings of traditional control strategies, this paper proposes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Based on the current setpoint y 0 , the compensator M −1 n generates the control value u n . The benefit of this technique especially appears when M −1 n represents the inverse non-linearities of the process P [27,28]. As noted in the previous section, there is only a small class of processes for which the analytical determination of the compensator is possible.…”
Section: Multi-loop Approachmentioning
confidence: 99%
“…Based on the current setpoint y 0 , the compensator M −1 n generates the control value u n . The benefit of this technique especially appears when M −1 n represents the inverse non-linearities of the process P [27,28]. As noted in the previous section, there is only a small class of processes for which the analytical determination of the compensator is possible.…”
Section: Multi-loop Approachmentioning
confidence: 99%
“…On the other hand, due to the coupling relationship between the output capacity of the unit and the fuel economy and the speed, the unit needs to switch to different target speed points frequently according to the driving demand [9][10][11][12]. In response to the above problems, scholars have proposed control strategies, such as constant speed QFT (Quantitative Feedback Theory) robust control, fuzzy control, and sliding mode control [13][14][15][16]. However, due to the characteristics of the ultralight power station system, such as small inertia, small capacity, high speed rating of the power generation unit, and unbuffered energy storage unit, the above strategies are not applicable.…”
Section: Introductionmentioning
confidence: 99%
“…No mechanical connection can be set between the engine and the transmission, and the engine speed and torque can be adjusted to make it work in the maximum efficiency zone. In recent years, the problem of coordination control of engine-generator sets used in many independent power systems' primary power sources at home and abroad has become increasingly prominent [13]. During the running of hybrid electric vehicles, the engine needs to switch the speed operating point according to the optimal fuel economy consumption following the control strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers found that for the generator sets that make up the vehicle's integrated power system: On the one hand, due to the efficiency of the installed capacity in the car, the power of the engine and the generator is roughly similar when the vehicle needs high-speed bending or rapid acceleration, the sudden increase in the load power of the vehicle may make the electromagnetic torque of the generator as a resistance moment exceed the engine output torque in a short time, and the connecting shaft of the power generation unit is mainly affected by the generator, resulting in the instability of the unit; On the other hand, due to the coupling relationship between the output capacity of the unit and the fuel economy and the speed, the unit needs to switch to different target speed points frequently according to the driving demand [9][10][11][12]. In response to the above problems, scholars have proposed control strategies such as constant speed QFT robust control, fuzzy control, and sliding mode control [13][14][15][16]. However, due to the characteristics of the ultra-light power station system, such as small inertia, small capacity, high rated speed of the power generation unit, and unbuffered energy storage unit, the above strategies are not applicable.…”
Section: Introductionmentioning
confidence: 99%